An intrinsic magnetic MOF catalyst for directional conversion of waste oil into bio-jet fuel and a preparation method and application thereof
Patent Information
- Application Number
- CN202611063698.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-07-17
- Publication Date
- 2026-10-09
AI Technical Summary
[0004]其一,产物碳链结构和异构化程度难以精准控制,诸如负载型Pt/SAPO-11、Ni/HZSM-5的分子筛催化剂,其孔道分布较宽且酸性位点不均一,在催化长链脂肪酸加氢异构化时,极易发生过度裂化,或生成双支链/多支链异构体,进而导致产品密度和冰点不合格;
[0041]本申请通过设计以Mn-Fe共掺杂MIL-53(Al)为骨架、Ni-Mo-B非晶态合金为限域封装活性组分的“三重功能协同”催化剂体系,从分子尺度突破了传统催化剂单一功能的局限,具体分析如下:
Smart Images

Figure SMS_1 
Figure SMS_2
Abstract
Description
Technical Field
[0001] This application relates to the field of renewable bioenergy technology, and more specifically, to an intrinsic magnetic MOF catalyst for the directional conversion of waste oil into biofuel, its preparation method, and its application. Background Technology
[0002] Waste oils, as an important raw material for renewable bioenergy, have always been supported by national policies for their resource utilization. Among them, bio-jet fuel is regarded as one of the important technical paths for achieving carbon emission reduction throughout the entire life cycle in the aviation field, namely, producing bio-jet fuel using waste oils as raw materials through hydrogenation deoxygenation-isomerization process.
[0003] However, this technology currently faces two major bottlenecks that severely restrict its application value:
[0004] Firstly, the carbon chain structure and degree of isomerization of the product are difficult to control precisely. For example, the molecular sieve catalysts such as supported Pt / SAPO-11 and Ni / HZSM-5 have a wide pore distribution and uneven acid sites. When catalyzing the hydrogenation isomerization of long-chain fatty acids, they are prone to over-cracking or generating bi-branched / multi-branched isomers, which in turn leads to unqualified product density and freezing point.
[0005] Secondly, the separation of catalysts from the reaction system is difficult, hindering continuous industrial operation. Although traditional fixed-bed catalysts do not require separation, they are prone to carbon buildup and deactivation due to high reaction temperatures. While fluidized bed or slurry bed processes have good mass transfer, ultrafine powder catalysts are difficult to recover through conventional filtration or sedimentation, resulting in high catalyst loss and high costs. Therefore, some companies have tried to combine magnetic materials with catalysts.
[0006] Although catalysts composed of magnetic materials have corresponding magnetic separation capabilities, such as conventional Fe3O4@MOF magnetic composite materials, their MOF shells are mostly ZIF-8 or MIL-101(Cr), with fixed pore sizes and no active sieving capabilities. They cannot selectively catalyze conversion based on product molecular size, and the coating layer is easily peeled off in high-temperature acidic environments, resulting in severe loss of magnetic cores.
[0007] Based on this, this application provides an intrinsic magnetic MOF catalyst for the directional conversion of waste oil into bio-jet fuel, its preparation method, and its application, aiming to simultaneously solve the technical problems of product selectivity control, catalyst separation, and stability. Summary of the Invention
[0008] To address the aforementioned technical issues, this application provides an intrinsic magnetic MOF catalyst for the directional conversion of waste oil into bio-jet fuel, along with its preparation method and application. Through the synergistic design of "intrinsic magnetism, window distortion, and confined encapsulation," it simultaneously achieves excellent magnetic recovery performance and long-term stability.
[0009] In a first aspect, this application provides an intrinsic magnetic MOF catalyst for the targeted conversion of waste oil into biofuel. The catalyst comprises:
[0010] The intrinsically magnetic MIL-53(Al) framework co-doped with Mn-Fe is self-assembled by aluminum, manganese, iron sources and mixed ligands via a hydrothermal method.
[0011] The active component of the Ni-Mo-B amorphous alloy is encapsulated within the pores of the skeleton.
[0012] The mixed ligand is composed of terephthalic acid H2BDC and 2,6-naphthalenedicarboxylic acid H2NDC mixed in a molar ratio of (4-6):1.
[0013] Preferably, in the Mn-Fe co-doping, the molar ratio of Al, Mn, and Fe is (8.5-9.5):(0.5-1):(0.5-1).
[0014] Preferably, the molar ratio of Ni to Mo in the Ni-Mo-B amorphous alloy is (8-12):1.
[0015] Secondly, this application provides a method for preparing an intrinsically magnetic MOF catalyst for the targeted conversion of waste oil into bio-jet fuel, comprising the following steps:
[0016] Hydrothermal synthesis of S1, Mn-Fe intrinsic magnetic MIL-53(Al) framework:
[0017] 1) Arrange the aluminum source, manganese source, and iron source according to Al 3+ Mn 2+ Fe 3+ The corresponding molar ratio dissolved in N,N-dimethylacetamide DMAc is denoted as solution A;
[0018] 2) Dissolve the main ligand H2BDC and the contractile ligand H2NDC in DMAc at the corresponding molar ratio, and add benzoic acid BA as a crystal growth regulator, denoted as solution B;
[0019] 3) Slowly pour solution B into solution A, stir, then add mineralizing agent HF dropwise, and transfer to a hydrothermal reactor;
[0020] 4) Heat to 200-220℃ and crystallize at a constant temperature for 48-72 hours; after natural cooling, wash and dry to obtain activated magnetic framework powder;
[0021] Confined reduction encapsulation of S2 and Ni-Mo-B amorphous alloys:
[0022] 1) Take the activated magnetic framework powder obtained from S1, disperse it in anhydrous ethanol, add nickel source and molybdenum source, and adjust the molar ratio of Ni to Mo to the corresponding values. Stir to allow metal ions to diffuse fully into the pores.
[0023] 2) Transfer the above suspension to an ice-water bath, and under the protection of an inert gas, slowly add an alkaline NaOH aqueous solution of NaBH4, keeping the system temperature ≤5℃ throughout the process;
[0024] 3) After the dripping is complete, continue stirring, use a strong magnet to adsorb and recover the black powder, wash and dry it to obtain the finished intrinsic magnetic MOF catalyst.
[0025] Preferably, the benzoic acid BA and Al in S1 3+ The molar ratio is (0.8-1.2):1;
[0026] The concentration of the mineralizing agent HF is 30-40%, and its addition amount is Al. 3+ 3-5% of the number of moles.
[0027] Preferably, the NaBH4 and Ni in S2 2+ The molar ratio is (3-5):1.
[0028] Preferably, the heating rate in S1 is 1-2℃ / min;
[0029] The washing process involves sequentially using DMAc, deionized water, and anhydrous ethanol.
[0030] The drying process involves vacuum drying at 160-180℃ for 12-15 hours.
[0031] Thirdly, this application provides an intrinsic magnetic MOF catalyst, or the product obtained by the above method, for the targeted conversion of waste oil into biofuel.
[0032] Preferably, a fixed-bed continuous reactor is used, and its process parameters are as follows:
[0033] Reaction temperature: 350-390℃;
[0034] System pressure: 4.0-7.0 MPa;
[0035] Mass hourly space velocity (WHSV): 0.8-1.2 h⁻¹;
[0036] Hydrogen-to-oil volume ratio: 800-1000:1;
[0037] Catalyst loading: 12g, mixed with 24g of quartz sand;
[0038] The raw material is pre-degummed and decolorized waste frying oil with an acid value ≤10mg KOH / g.
[0039] Preferably, the catalyst after reaction deactivation is magnetically separated and recovered by applying an external magnetic field of ≥8000Gs. The separated catalyst is then reused after being calcined in air at 350-450℃ to remove carbon and regenerated by hydrogen reduction at 350-450℃.
[0040] In summary, this application has the following beneficial effects:
[0041] This application presents a "triple-functional synergistic" catalyst system designed with Mn-Fe co-doped MIL-53(Al) as the framework and Ni-Mo-B amorphous alloy as the confined encapsulated active component. This system overcomes the limitations of traditional single-function catalysts at the molecular scale. The specific analysis is as follows:
[0042] 1) Intrinsic magnetism, rather than an external magnetic core: directly through the metal nodes of the MIL-53 (Al) framework, with trace amounts of Mn 2+ and Fe 3+ Replace part of Al 3+ The superexchange interaction between Mn-Fe clusters is used to make the entire MOF crystal intrinsically paramagnetic / weakly ferromagnetic. Magnetic elements can be directly embedded into the framework nodes and become part of the framework structure, which fundamentally eliminates the problem of magnetic core stripping.
[0043] 2) In-situ window distortion shrinkage, rather than chemical grafting: By introducing 2,6-naphthalenedicarboxylic acid, which has greater rigidity, and conventional terephthalic acid in a specific molar ratio to form a mixed ligand co-crystal during the ligand synthesis stage, the steric hindrance of the naphthalene ring of NDC will force the framework window to undergo "asymmetric distortion".
[0044] Its effective pore size is precisely compressed from 8.6 Å to 6.0 ± 0.2 Å. This pore size is just larger than the kinetic diameter of n-alkane, allowing it to freely enter the pore and undergo hydrogenation isomerization; at the same time, it is smaller than the critical diameter of the dibranched isomer, preventing it from diffusing out and causing it to be further broken down into smaller molecules or forcibly converted into a monobranched isomer, thereby greatly improving the selectivity of the monobranched isomer.
[0045] 3) Amorphous Ni-Mo-B alloy confined encapsulation: In the activated channels after hydrothermal synthesis of MOF, amorphous Ni-Mo-B alloy can be generated in situ by low-temperature reduction with NaBH4. This alloy has both dehydrogenation / hydrogenation activity and certain isomerization acidity. Moreover, the amorphous structure avoids the use of precious metals. More importantly, the physical confinement effect of the channels effectively inhibits the crystallization and sintering of the amorphous alloy in high-temperature reactions, which significantly improves the stability of long-term operation.
[0046] Furthermore, the Ni-Mo-B amorphous alloy in this application is encapsulated within the framework channels by a low-temperature confined reduction method, forming a nano-confined catalytic reaction microenvironment. Based on this mechanism, after 300 hours of long-term operation, the conversion rate decrease can be controlled within 5%, which is far superior to the attenuation rate of more than 8% in the prior art. Moreover, thanks to the intrinsic magnetic framework design rather than the added Fe3O4 core, the catalyst of this application exhibits excellent magnetic stability in a high-temperature acidic reaction environment. Detailed Implementation
[0047] The present application will be further described in detail below with reference to the embodiments.
[0048] Main raw material sources and specifications:
[0049] Unless otherwise specified, the raw materials used in the following preparation examples and embodiments are all commercially available industrial grade or analytical grade products. The specific sources and specifications are shown in the table below:
[0050]
[0051] Preparation Example 1
[0052] The preparation method of the precursor solution for the intrinsically magnetic Mn-Fe MIL-53 (Al) framework is as follows:
[0053] 1) Preparation of metal salt solution: Weigh 21.74g AlCl3·6H2O, 0.99g MnCl2·4H2O, and 1.35g FeCl3·6H2O, dissolve them in 600mL N,N-dimethylacetamide DMAc, and stir magnetically at room temperature until completely dissolved to obtain a clear metal salt solution A;
[0054] Al in the above doping process 3+ Mn 2+ Fe 3+ The molar ratio is 9:0.5:0.5;
[0055] 2) Preparation of mixed ligand solution: Weigh 16.61g H2BDC, 4.33g H2NDC, corresponding to a molar ratio of terephthalic acid to 2,6-naphthalenedicarboxylic acid of 5:1, and 12.2g benzoic acid BA, dissolve in 200mL N,N-dimethylacetamide DMAc, heat to 60℃ and stir until completely dissolved to obtain mixed ligand solution B.
[0056] Performance testing
[0057] The catalysts prepared in each example and comparative example were used as test objects. 12g of each catalyst was mixed with 24g of quartz sand and then packed into the isothermal zone of the fixed bed continuous reactor.
[0058] Then, using pre-degummed and decolorized waste oil with an acid value ≤10mg KOH / g as raw materials, the hydroisomerization reaction was evaluated under the following process conditions:
[0059] Reaction temperature: 370±2℃;
[0060] System pressure: 5.5 MPa;
[0061] Mass hourly space velocity (WHSV): 1.0 h -1 ;
[0062] Hydrogen-to-oil volume ratio: 900:1;
[0063] After 100 hours of stable operation, the liquid products from each evaluation device were collected for product distribution testing.
[0064] After 300 hours of continuous operation, the decrease in the total conversion rate of raw materials on each catalyst was recorded;
[0065] Meanwhile, the mixture of each reacted catalyst and quartz sand was placed in a drum magnetic separator with a magnetic field strength of 8000 Gs, and the magnetic recovery rate of each catalyst was calculated.
[0066] Then, using the collected liquid products and recovered catalyst samples as test objects, the following performance tests were conducted:
[0067] 1) Product distribution test: The liquid products were analyzed by simulated distillation combined with gas chromatography-mass spectrometry (GC-MS) according to the method in ASTM D2887;
[0068] Calculate C in the liquid products respectively 15 -C 18 Isomerized alkane mass percentage (jet fuel composition), single-branched isomer percentage (relative to total isomers), cracking products (C8-C) 12 ) percentage.
[0069] 2) Magnetic recovery rate test: The catalyst and quartz sand mixture after reaction were placed in a drum magnetic separator with a magnetic field strength of 8000Gs, and the mass ratio of the adsorbed and recovered catalyst to the total catalyst was calculated.
[0070] 3) Stability test: Under the above fixed bed evaluation conditions, record the decrease (%) of the total conversion rate of feedstock on each catalyst after 300 hours of stable operation.
[0071] Example 1
[0072] An intrinsically magnetic MOF catalyst for the targeted conversion of waste oil into biofuel comprises: an intrinsically magnetic MIL-53(Al) framework co-doped with Mn-Fe, and an amorphous Ni-Mo-B alloy active component encapsulated within the pores of the framework, and is prepared by the following method:
[0073] Hydrothermal Synthesis of S1, Mn-Fe Intrinsic Magnetic MIL-53(Al) Framework
[0074] 1) Slowly pour the mixed ligand solution B obtained in Preparation Example 1 into the metal salt solution A of Solution A, and continuously stir magnetically for 30 minutes until a homogeneous mixture is formed;
[0075] 2) Add mineralizing agent HF dropwise to the above mixture. The concentration of mineralizing agent HF is 40%, and the solvent is water. The amount added is Al. 3+ Add 5% of the molar amount and continue stirring for 15 minutes to obtain a suspension;
[0076] 3) Transfer the obtained suspension to a 1L hydrothermal reactor, raise the temperature to 220℃ at a rate of 1℃ / min, maintain the constant temperature, and crystallize for 72 hours.
[0077] 4) After naturally cooling to room temperature, wash three times each with DMAc, deionized water and anhydrous ethanol, and finally dry in a vacuum drying oven at 180℃ for 12 hours to obtain activated magnetic framework powder.
[0078] Confined reduction encapsulation of S2 and Ni-Mo-B amorphous alloys
[0079] 1) Take 10g of the activated magnetic framework powder obtained from S1, disperse it in 200mL of anhydrous ethanol, and add NiCl2·6H2O and ammonium molybdate to make the molar ratio of Ni to Mo 10:1. Stir magnetically for 6 hours.
[0080] 2) Transfer the suspension obtained in 1) above to an ice-water bath (0℃), and under nitrogen protection, slowly add an alkaline aqueous solution of NaBH4 and NaOH at a rate of 0.5 mL / min, while controlling the reaction between NaBH4 and Ni. 2+ The molar ratio is 5:1, and the system temperature is kept ≤5℃ during the dropping process;
[0081] 3) After the NaOH alkaline aqueous solution of NaBH4 in 2) has been added dropwise, continue stirring for 2 hours. After the reaction is completed, use a strong magnet to adsorb and recover the black powder, wash it 3 times each with deoxygenated deionized water and deoxyethanol, and dry it under vacuum at 60°C for 6 hours to obtain the intrinsic magnetic MOF catalyst.
[0082] Example 2
[0083] An intrinsically magnetic MOF catalyst for the targeted conversion of waste oil into biofuel differs from Example 1 in that only the mixed ligand solution used is different, as detailed below:
[0084] The amount of 2,6-naphthalenedicarboxylic acid H2NDC used was 5.20g, that is, the molar ratio of terephthalic acid to 2,6-naphthalenedicarboxylic acid was 4:1, and the other steps and conditions were exactly the same as in Example 1.
[0085] Example 3
[0086] An intrinsic magnetic MOF catalyst for the directional conversion of waste oil into bio-jet fuel differs from Example 1 only in the operating conditions of step 1) in S2. When encapsulating Ni-Mo-B, the molar ratio of Ni to Mo is adjusted to 8:1. The other steps and conditions are exactly the same as in Example 1.
[0087] Example 4
[0088] An intrinsic magnetic MOF catalyst for the directional conversion of waste oil into bio-jet fuel differs from Example 1 only in the operating conditions of step 1) in S2. When encapsulating Ni-Mo-B, the molar ratio of Ni to Mo is adjusted to 12:1. The other steps and conditions are exactly the same as in Example 1.
[0089] Example 5
[0090] An intrinsically magnetic MOF catalyst for the targeted conversion of waste oil into biojet fuel differs from Example 1 only in that the metal salt solution used is different, and its Al... 3+ Mn 2+ Fe 3+ The molar ratio was adjusted to 8.5:0.75:0.75, and the other steps and conditions were exactly the same as in Example 1.
[0091] Comparative Example 1
[0092] A catalyst for the targeted conversion of waste oil into bio-jet fuel, differing from Example 1 in that only the mixed ligand solution used is different, as detailed below:
[0093] The amount of 2,6-naphthalenedicarboxylic acid H2NDC used was 0 g, that is, the molar ratio of terephthalic acid to 2,6-naphthalenedicarboxylic acid was 5:0. Other steps and conditions were exactly the same, and the resulting product was counted as catalyst D1.
[0094] Comparative Example 2
[0095] A catalyst for the targeted conversion of waste oil into bio-jet fuel, differing from Example 1 in that only the metal salt solution used is different, as detailed below:
[0096] It is free of Mn and Fe doping, i.e., the molar ratio of Al3+:Mn2+:Fe3+ is 10:0:0. The other steps and conditions are exactly the same as in Example 1, and the resulting product is considered as catalyst D2.
[0097] Comparative Example 3
[0098] A catalyst for the directional conversion of waste oil into bio-jet fuel differs from Example 1 in that only S2 does not contain the addition of NiCl2·6H2O and ammonium molybdate, and the framework is treated only with NaBH4. All other steps and conditions are exactly the same, and the resulting product is designated as catalyst D3.
[0099] Comparative Example 4
[0100] A catalyst for the targeted conversion of waste oil into bio-jet fuel, differing from Example 1 in that Ni is used only during the hydrothermal synthesis in S1. 2+ and Mo 6+ Salt directly with Al 3+ The salt and mixed ligands are mixed in one step, that is, the active component is directly introduced in the skeleton synthesis stage and no confined reduction encapsulation step of S2 is performed subsequently. All other steps and conditions are exactly the same, and the resulting product is counted as catalyst D4.
[0101] Comparative Example 5
[0102] A catalyst for the targeted conversion of waste oil into bio-jet fuel differs from Example 1 only in the encapsulation method of step 1) in S2, as follows:
[0103] The active Ni-Mo-B component is loaded onto the framework obtained in S1 by conventional equal-volume impregnation method, instead of in-situ reduction and encapsulation. The NaBH4 reduction operation in step 2) of S2 is not performed. All other steps and conditions are exactly the same. The resulting product is called catalyst D5.
[0104] The catalysts and corresponding products prepared in Examples 1-5 and Comparative Examples 1-5 were selected as test objects, and their product distribution, magnetic recovery rate and stability were tested respectively. The results are recorded in the table below.
[0105] Table: Performance test results of Examples 1-5 and Comparative Examples 1-5
[0106]
[0107] As can be seen from the data in Examples 1-5 above, the catalyst prepared in this application exhibits excellent performance in terms of product selectivity, magnetic recovery rate, and long-term stability. Furthermore, the comparison between the examples and the comparative examples further verifies the indispensability of each function in the triple functional synergistic mechanism.
[0108] The following analysis focuses on the core bottlenecks of existing technologies, using data from this application:
[0109] I. Addressing the pain point of "difficulty in precisely controlling the carbon chain structure and isomerization degree of the product":
[0110] 1) This application introduces 2,6-naphthalenedicarboxylic acid, which has greater rigidity, and terephthalic acid into a mixed ligand co-crystallization during the ligand synthesis stage. By utilizing the steric hindrance of the NDC naphthalene ring, the window of the MIL-53(Al) framework is forced to undergo "asymmetric distortion", and the effective pore size is precisely compressed from 8.6 Å to 6.0 ± 0.2 Å.
[0111] The aforementioned pore size is just larger than the kinetic diameter of n-alkane (4.9 Å), allowing it to freely enter the pores and undergo hydrogenation isomerization; at the same time, it is smaller than the critical diameter of the dibranched isomer (7.0 Å), preventing it from diffusing out and causing it to be further broken down into smaller molecules or forcibly converted into a monobranched isomer.
[0112] Comparative Example 1, due to the complete absence of NDC contractile ligands, retains the original pore size of MIL-53(Al) at 8.6 Å, thus its C 15 -C 18 Isomers accounted for 45.2%, single-branched isomer selectivity was 58.6%, while cracking products accounted for as much as 18.5%.
[0113] In contrast, in Example 1, after introducing a mixed ligand of BDC:NDC = 5:1, C 15 -C 18 The proportion of isoalkanes increased to 67.8%, the selectivity of single-branched isomers jumped to 84.2%, and the cracking products decreased sharply to 6.5%, which shows that the design of the window distortion function is a necessary means to achieve the effect of this application.
[0114] The root cause of these significant differences lies in the fact that the original 8.6 Å wide pore size cannot perform size screening of isomerization products. While n-alkanes can freely enter, both the single-branched and double-branched isomers can also freely diffuse out of the pore. After leaving the pore, the double-branched isomer remains exposed to acidic sites on the outer surface of the framework, making it highly susceptible to over-cracking and generating a large amount of C8-C. 12 Light components;
[0115] When this application utilizes the molecular sieving effect of precisely compressing the pore size using NDC mixing, single-branched isomers can diffuse smoothly out of the pores and be retained, while double-branched isomers are trapped in the pores and can only escape after undergoing β-cleavage or isomer rearrangement at acidic sites to become single-branched isomers. This mechanism significantly improves the selectivity of single-branched isomers while significantly reducing cracking products.
[0116] 2) A comparison between Example 1 and Example 2 demonstrates the importance of fine balance in pore size control. When the NDC ratio increases from 5:1 to 4:1, the pore size further shrinks. Data shows that: C 15 -C 18 The proportion of isoalkanes further increased from 67.8% to 71.2%, while cracking products decreased from 6.5% to 5.8%, but single-branch selectivity slightly decreased from 84.2% to 81.5%.
[0117] This phenomenon indicates that while further shrinkage of the pore size continues to inhibit cracking, it also begins to slightly hinder the diffusion of monobranched products. Some monobranched isomers may undergo secondary reactions due to prolonged residence time caused by excessively tight pore size. It is evident that there is an optimal window for the BDC:NDC ratio, which is sufficient to screen out dibranched isomers without excessively hindering the escape of monobranched isomers.
[0118] 3) A comparison between Example 3 and Example 4 shows that the Ni / Mo ratio isomerization selectivity also has a synergistic regulatory effect. When the Ni:Mo ratio is adjusted from 10:1 to 8:1, the single-branch selectivity further increases from 84.2% to 86.1%, but C 15 -C 18 The total proportion of isoalkanes decreased from 67.8% to 64.5%, while cracking products slightly increased from 6.5% to 7.2%. However, when the Ni:Mo ratio was adjusted to 12:1, the single-branch selectivity rebounded to 82.5%. 15 -C 18 The proportion of isoalkanes further decreased to 63.0%;
[0119] The principle behind the aforementioned data changes lies in the fact that in Ni-Mo-B amorphous alloys, the Mo component not only participates in the formation of the alloy structure, but its oxide morphology also provides certain Lewis acid sites, which are conducive to the carbocation isomerization reaction. Therefore, when the Mo content is relatively high, the density of acid sites increases, promoting the isomerization depth and improving the single-branch selectivity. However, excessive acidity can also trigger slight cracking side reactions, leading to C 15 -C 18 The overall proportion decreases. Conversely, when the Mo content is too low, the isomerization activity is insufficient and the selectivity decreases. Based on this, the optimal Ni / Mo ratio is derived.
[0120] In summary, through the longitudinal comparison of Examples 1-4 with Comparative Example 1, and the lateral comparison among Examples 1-4, a clear conclusion can be drawn: NDC-induced window distortion and pore shrinkage is the core means to achieve "lock-and-key" precise catalysis, while the Ni-Mo-B composition ratio provides a synergistic tool for finely controlling the isomerization depth. Together, they achieve the optimal balance between jet fuel yield and isomer selectivity.
[0121] II. Addressing the pain point of "difficulty in separating the catalyst from the reaction system"
[0122] 1) This application utilizes trace amounts of Mn in the metal nodes (µ-OH-Al chains) of the MIL-53 (Al) framework. 2+ and Fe 3+ Replace part of Al 3+ The superexchange interaction between Mn-Fe clusters is used to make the entire MOF crystal intrinsically paramagnetic / weakly ferromagnetic, thus completely abandoning the traditional route of adding Fe3O4 nanoparticles.
[0123] The data from Comparative Example 2 positively validates the above viewpoint. In the case of no Mn-Fe doping, Comparative Example 2's product selectivity is essentially equivalent to that of Example 1. 15 -C 18 The proportion of isoalkanes was 66.5%, the single-branch selectivity was 83.5%, and the cracking products were 6.8%, indicating that Mn-Fe doping had no negative impact on the catalytic activity of the MIL-53 (Al) framework, and its pore structure and acidic sites were stable.
[0124] However, the magnetic recovery rate of Comparative Example 2 was only 12.8%, which is more than 80 percentage points higher than the magnetic recovery rates of 95.5%-97.5% in Examples 1-5. This strongly proves that the magnetic recovery performance of this application comes entirely from the intrinsic magnetism generated by Mn-Fe co-doping, and not from any other factors. The principle is derived as follows:
[0125] In the µ-OH-Al chain of MIL-53(Al), Al 3+ Mn 2+ and Fe 3+ After partial substitution, superexchange interactions occur between adjacent Mn and Fe ions through hydroxyl bridges, resulting in long-range magnetic order in the entire framework. This magnetism is intrinsic, meaning that the magnetic ions are themselves part of the MOF framework, rather than being external magnetic particles. This configuration is fundamentally different from the Fe3O4@MOF core-shell structure in the prior art: the latter relies on the physical coating between the external magnetic core and the MOF shell, resulting in poor interface stability; while the former covalently embeds magnetic elements into the framework nodes, integrating magnetism and structure.
[0126] 2) Through data comparison in Example 5, it can also be seen that the doping ratio regulates the magnetic recovery performance. When the Al:Mn:Fe ratio is adjusted from 9:0.5:0.5 in Example 1 to 8.5:0.75:0.75, the magnetic recovery rate increases from 96.3% to 97.5%, while C... 15 -C 18 The selectivity indicators such as the proportion of isoparaffins, single-branched selectivity, and cracking products are basically the same as those in Example 1.
[0127] The above results indicate that appropriately increasing the Mn-Fe doping amount can further enhance the magnetic response intensity without sacrificing catalytic performance. Therefore, it can be concluded that the optimal range of Al:Mn:Fe = (8.5-9.5):(0.5-1):(0.5-1) is a reasonable choice that combines magnetic properties and catalytic activity.
[0128] Furthermore, it should be particularly noted that the data in Comparative Example 2 also demonstrate that the intrinsic magnetic configuration of this application, namely the Mn-Fe doped MIL-53 (Al) framework, is substantially different from the existing configuration of an externally added Fe3O4 magnetic core + MOF shell in terms of physical configuration and chemical composition. That is, the former is a magnetic element covalently embedded in the framework node, while the latter is a magnetic particle physically encapsulated inside the shell.
[0129] III. Addressing the pain points of "poor catalyst stability and easy deactivation of active components"
[0130] 1) This application generates an in-situ Ni-Mo-B amorphous alloy in the activated channels after hydrothermal synthesis of MOF by low-temperature (≤5℃) NaBH4 reduction, thereby achieving confined encapsulation of active components in nanopores. Comparison of various embodiments and comparative examples shows that confined encapsulation is a necessary process.
[0131] Comparative Example 3, lacking the addition of NiCl2·6H2O and ammonium molybdate, and only treating the framework with NaBH4, did not meet the conditions for Ni-Mo-B alloy formation, and its C 15 -C 18 The proportion of isoalkanes was only 8.9%, and the single-branch selectivity was only 35.0%, far lower than 67.8% and 84.2% in Example 1;
[0132] The above results indicate that the MIL-53(Al) framework itself is extremely weakly acidic and has almost no ability to convert long-chain n-alkanes into isoalkanes. Without the Ni-Mo-B alloy to provide hydrogenation and dehydrogenation activity and isomerization acidity, even the most precise 6.0Å pore size after NDC shrinkage is "like a skilled cook without rice".
[0133] More importantly, the cracking products of Comparative Example 3 were only 4.2%, which does not mean good selectivity, but rather that there were simply not enough isomerization products generated, and the cracking reaction was "unable to produce anything". This data proves from the opposite perspective the essential logic of the synergistic triple function of this application: the hydroisomerization activity is "1", and the shape selectivity is the "0" that follows. Without "1", the "0" alone is meaningless.
[0134] 2) Comparative Example 4, in the hydrothermal synthesis stage, Ni... 2+ and Mo 6+ Salt directly with Al 3+The salt and mixed ligands are mixed in one step, meaning the active component is introduced during the scaffold synthesis stage, omitting the subsequent S2 confinement reduction encapsulation step. Its C 15 -C 18 The proportion of isoalkanes plummeted to 28.5%, the single-branch selectivity was only 52.0%, the cracking products were as high as 15.0%, and the conversion rate decreased by 25.0% after 300 hours.
[0135] The root cause of this performance degradation lies in: Ni 2+ and Mo 6+ Ions interfere with the nucleation and crystallization of Al in MIL-53 (Al). 3+ Coordination self-assembly with ligands leads to incomplete framework crystallization and disruption of pore regularity. Simultaneously, the introduction of transition metal ions under high-temperature hydrothermal conditions may induce side reactions, generating impurity phases. This result fully demonstrates that a regular intrinsic magnetic MIL-53(Al) framework must first be formed, followed by confined reduction within the already formed regular pores to generate a Ni-Mo-B alloy—that is, "nucleation first, then encapsulation"—and the two processes must be separated in time and space.
[0136] 3) As can be seen from the data of Comparative Example 5, confined encapsulation has dual advantages over conventional impregnation in terms of initial selectivity and long-term stability. Comparative Example 5 only uses the conventional equal-volume impregnation method to load the Ni-Mo-B active component onto the framework obtained in S1, without NaBH4 reduction; its C 15 -C 18 The proportion of isoalkanes was 48.0%, the single-branch selectivity was 68.0%, the cracking products were as high as 14.0%, and the conversion rate decreased by 18.0% after 300h.
[0137] The principle behind the above significant differences is that conventional impregnation methods cause the Ni-Mo-B active components to be deposited mainly on the outer surface of the framework rather than inside the pores. The metal sites on the outer surface are not limited by the pore size and do not have shape selectivity for the hydrogenation / isomerization of n-alkanes. Both n-alkanes and isomerization products can react freely on them, resulting in the generation of a large number of bibranched isomers and subsequent external cracking.
[0138] Meanwhile, metal particles lacking physical constraints of pores are prone to migration, agglomeration, and sintering under high-temperature reaction conditions of 370℃, resulting in a sharp decrease in active surface area and severe degradation of conversion rate over 300h. Therefore, it is urgent to use the confined reduction encapsulation process in this application. The process in this application enables Ni-Mo-B alloy to be generated in situ inside nanopores with a pore size of only 6.0Å, and ensures that its particle size is physically confined to the nanoscale (<6.0Å) by the geometry of the pores, making it less prone to agglomeration and growth. At the same time, each metal particle is isolated from each other by the framework pores, physically eliminating sintering channels.
[0139] It should also be specifically pointed out that, due to limitations in experimental costs, patent priority time limits, and the general understanding of parameter response patterns by those skilled in the art, this specification only uses Examples 1-5 as representatives for detailed experimental verification, and should not be regarded as a limitation on the scope of this application.
[0140] Furthermore, based on the MOF framework doping mechanism, mixed ligand window distortion principle, confined reduction encapsulation process, and synergistic effect between various functions that have been fully disclosed in this specification, those skilled in the art can reasonably expect without objection that excellent and consistent results can be obtained within the preferred parameter range.
[0141] The above are all modifications that can be made to this embodiment without contributing any inventive step, or solutions that clearly constitute technical teaching, after reading this specification. However, as long as they are within the scope of the claims of this application, they should be protected by patent law.
Claims
1. An intrinsically magnetic MOF catalyst for the targeted conversion of waste oil into biofuel, characterized in that, The catalyst comprises: The intrinsically magnetic MIL-53(Al) framework co-doped with Mn-Fe is self-assembled by aluminum, manganese, iron sources and mixed ligands via a hydrothermal method. The active component of the Ni-Mo-B amorphous alloy is encapsulated within the pores of the skeleton. The mixed ligand is composed of terephthalic acid H2BDC and 2,6-naphthalenedicarboxylic acid H2NDC mixed in a molar ratio of (4-6):
1.
2. The intrinsic magnetic MOF catalyst for the targeted conversion of waste oil into biofuel as described in claim 1, characterized in that, In the Mn-Fe co-doping, the molar ratio of Al, Mn, and Fe is (8.5-9.5):(0.5-1):(0.5-1).
3. The intrinsic magnetic MOF catalyst for the targeted conversion of waste oil into biofuel as described in claim 2, characterized in that: The molar ratio of Ni to Mo in the Ni-Mo-B amorphous alloy is (8-12):
1.
4. The method for preparing the intrinsic magnetic MOF catalyst for the directional conversion of waste oil into biofuel as described in any one of claims 1-3, characterized in that, Includes the following steps: Hydrothermal synthesis of S1, Mn-Fe intrinsic magnetic MIL-53(Al) framework: 1) Arrange the aluminum source, manganese source, and iron source according to Al 3+ Mn 2+ Fe 3+ The corresponding molar ratio dissolved in N,N-dimethylacetamide DMAc is denoted as solution A; 2) Dissolve the main ligand H2BDC and the contractile ligand H2NDC in DMAc at the corresponding molar ratio, and add benzoic acid BA as a crystal growth regulator, denoted as solution B; 3) Slowly pour solution B into solution A, stir, then add mineralizing agent HF dropwise, and transfer to a hydrothermal reactor; 4) Heat to 200-220℃ and crystallize at a constant temperature for 48-72 hours; after natural cooling, wash and dry to obtain activated magnetic framework powder; Confined reduction encapsulation of S2 and Ni-Mo-B amorphous alloys: 1) Take the activated magnetic framework powder obtained from S1, disperse it in anhydrous ethanol, add nickel source and molybdenum source, and adjust the molar ratio of Ni to Mo to the corresponding values. Stir to allow metal ions to diffuse into the pores. 2) Transfer the above suspension to an ice-water bath, and under the protection of an inert gas, slowly add an alkaline NaOH aqueous solution of NaBH4, keeping the system temperature ≤5℃ throughout the process; 3) After the dripping is complete, continue stirring, use a strong magnet to adsorb and recover the black powder, wash and dry it to obtain the finished intrinsic magnetic MOF catalyst.
5. The method for preparing the intrinsic magnetic MOF catalyst for the directional conversion of waste oil into bio-jet fuel according to claim 4, characterized in that: Benzoic acid BA and Al mentioned in S1 3+ The molar ratio is (0.8-1.2):1; The concentration of the mineralizing agent HF is 30-40%, and its addition amount is Al. 3+ 3-5% of the number of moles.
6. The method for preparing the intrinsic magnetic MOF catalyst for the directional conversion of waste oil into bio-jet fuel according to claim 4, characterized in that: NaBH4 and Ni mentioned in S2 2+ The molar ratio is (3-5):
1.
7. The method for preparing the intrinsic magnetic MOF catalyst for the directional conversion of waste oil into bio-jet fuel according to claim 4, characterized in that: The heating rate described in S1 is 1-2℃ / min; The washing process involves sequentially using DMAc, deionized water, and anhydrous ethanol. The drying process involves vacuum drying at 160-180℃ for 12-15 hours.
8. The application of the intrinsic magnetic MOF catalyst according to any one of claims 1-3, or the product obtained by the method according to any one of claims 4-7, in the directional conversion of waste oil into biofuel.
9. The application according to claim 8, characterized in that, A fixed-bed continuous reactor is used, and its process parameters are as follows: Reaction temperature: 350-390℃; System pressure: 4.0-7.0 MPa; Mass hourly space velocity (WHSV): 0.8-1.2 h⁻¹; Hydrogen-to-oil volume ratio: 800-1000:1; Catalyst loading: 12g, mixed with 24g of quartz sand; The raw material is pre-degummed and decolorized waste frying oil with an acid value ≤10mg KOH / g.
10. The application according to claim 8, characterized in that, The deactivated catalyst is magnetically separated and recovered by applying an external magnetic field of ≥8000Gs. The separated catalyst is then regenerated by air roasting at 350-450℃ to remove carbon and hydrogen reduction at 350-450℃ before being reused.